INTERNALISASI NILAI-NILAI PENDIDIKAN AGAMA ISLAM DI SMK ABDI NEGARA TUBAN - Dian Ika Novita Sari; Moch Bahrurrosyadi Amrulloh (MIYAH : Jurnal Studi Islam, 2020)
Abstract: This study includes several reviews of the strategy to internalize the values of Islamic religious education along with the stages in the internalization process itself which includes the values of faith, moral values, and worship values. Given that the development of the times, the more widespread moral crisis experienced by most adolescents, especially students, this strategy aims to minimize unwanted events. This research uses descriptive qualitative research methods by using the exposure or depiction of facts, properties, and relationships between the phenomena studied in the form of writing or words and then carried out assessment or analysis. The results of this study show that the reality of the strategy of internalizing Islamic religious education values is very helpful in forming the character of the nation's children significantly packaged in PAI and Budi Pekerti subjects in class. So this internalization strategy is highly recommended in the application of the learning process because it is easy and the material delivered is more quickly captured.Keyword: Internalization, Islamic Education Values